Argumentation in Political Interview: Critical Discourse Analysis of Abdurrahman Wahid’s Controversial Regime - Yuniar Rachmawati Putri (Universitas Brawijaya, 2018)
Abdurrahman Wahid (Gus Dur) was dismissed as a president in 2001 due to his controversial acts. Australia Corporation (2001) conducted political interview to talk about his dismissal and the parliament, which against him. This article observes microstructure analysis in Abdurrahman Wahid interview. It presents a new way to analyse the Microstructures by providing the reader with illocutionary act analysis as well to support the ‘Action’ of the discourse (Wahid’s utterances). Humanism thought, which underlies his positive actions towards his dismissal, is used. Six values of Wahid are divinity, humanity, justice, equality, liberty, and local wisdom. Then, his leadership is worth appreciating as a charismatic leadership due to his positive (humanism) actions. Findings show that Wahid uses the positive acts toward his dismissal and people who against him. This article suggests for the future researchers to discuss more detail about the whole theory of Teun Van Dijk (Macrostructures, Microstructures and Superstructures).